Solar powered adsorption desalination system employing CPO-27(Ni). (September 2022) - Ghazy, Mohamed; Askalany, Ahmed A.; Ibrahim, E.M.M.; Mohamed, A.S.A.; Ali, Ehab S.; AL-Dadah, Raya
Abstract: Adsorption-based desalination system (ADS) is an alternative technology to the traditional water desalination systems as low-temperature sources can operate it. Also, ADSs use environmentally friendly materials, limiting global warming and environmental pollution. This work investigates the performance parameters of ADS powered by an evacuated thermal solar collector theoretically and experimentally. The system uses an advanced sorption material of metal-organic frameworks called CPO-27(Ni). The study estimates optimal operating conditions of ADS under the climate of Egypt. A mathematical model is carried out using MATLAB integrated with TRNSYS software. The study investigates high system performance through two modes; without heat recovery (Mode-1) and heat recovery (Mode-2). The ADS performance is evaluated by specific daily water production (SDWP) and gain output ratio (GOR) parameters. The results show a remarkable superiority for mode-2 as it achieved 10 (m 3 /ton-day) SDWP and 0.4 GOR, while mode-1 achieved about 5 (m 3 /ton-day) SDWP and 0.23 GOR at the optimum operating conditions. The improvement ratio using mode-2 reached 88 % of SDWP and 79 % of GOR. Also, the validation results showed a good qualitative and quantitative agreement between the experimental and theoretical data. Highlights: Solar adsorption desalination system is investigated. CPO-27(Ni) adsorbent is employed with and without heat recovery. SDWP and GOR achieved 10 m 3 /ton-day and 0.4, respectively. SDWP and GOR are improved by 88 % of and 79 % of GOR.